Vasoactive Hormones and the Diabetic Kidney. (2008) - Maric, Christine
Abstract : Diabetic nephropathy is the single most common cause of end-stage renal disease (ESRD) and accounts for significant morbidity and mortality. While the incidence of ESRD increased dramatically in the 1980s and 1990s, the U.S. Renal Data System (USRDS) 2005 Annual Data Report shows that 338 out of every million Americans had kidney failure in 2003, down slightly from 340 per million in 2002. This report shows that the numbers of people developing ESRD have stabilized despite the persistent increase in the number of people diagnosed with type 2 diabetes mellitus (T2DM). These data attest to both the efficacy of the currently available therapeutic regimens for the treatment of ESRD as well as better overall patient care. Unfortunately, these encouraging statistics do not apply to all patients. According to the USRDS report, the most marked ESRD decrease was seen in young Caucasian men (<40 years of age), while in other patient groups, particularly African Americans, ESRD has not changed much at all. These observations suggest that more in-depth studies, addressing specific issues, such as race, are needed to understand the disease process fully in order to create novel therapeutic strategies to eradicate the disease completely in all patient populations. The most commonly used therapeutic treatments for diabetic nephropathy are angiotensin-converting enzyme (ACE) inhibitors and angiotensin II (Ang II) receptor blockers (ARBs), implicating the importance of the renin-angiotensin-aldosterone system (RAAS) in the pathophysiology of diabetic nephropathy. The RAAS is not the only vasoactive hormonal system that is involved in the disease process. Over the past decade, studies have suggested that other vasoactive hormones, including endothelin, urotensin II, and the kallikrein-kinin system (KKS), are instrumental in mediating structural and functional alterations in the renal vasculature and parenchyma, leading to the development and progression of diabetic nephropathy. This review will summarize our current understanding of the contribution of vasoactive hormones in the pathophysiology of diabetic nephropathy with specific emphasis on the RAAS, especially the more recently identified components of this hormonal pathway.